Who Can Explain The Mauritian Miracle : Meade, Romer, Sachs or Rodrik? - Subramanian, Arvind; Roy, Devesh (Washington, D.C. : International Monetary Fund, 2001)
This paper examines different explanations-initial conditions, openness to trade and FDI, and institutions-of the Mauritian growth experience since the mid-1970s. We show that arguments based on openness to trade and FDI are either misleading or incomplete, and the transmission mechanism insufficiently identified. However, even when correctly articulated, openness appears to be a proximate rather than an underlying explanation for the Mauritian experience. The institution-based explanation offers greater promise. Ultimately, however, the econometric results indicate that existing explanations may be incomplete. Some idiosyncratic factors, particularly Mauritian diversity and the responses to managing it, may provide the missing pieces in the story of Mauritius's success.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet